Faktor – Faktor Yang Berhubungan Dengan Lama Hari Rawat Inap Studi Kasus Pada Perusahaan X Di PT Asuransi Intra Asia - Nurmawaty, Dwi; Fresitinawati, Senintyas; Rosdiana, Hafsha (Health Publica, 2024)
The use of PPE plays an important role in protecting the body from work hazards which can cause disease or work accidents in gas station operators. The use of PPE in operators is driven by various factors including workers' knowledge and supervision carried out by field supervisors. This research aims to determine the relationship and description between knowledge and supervision and behavior in using personal protective equipment (PPE) at gas stations. This research was conducted at SPBU X Cengkareng, West Jakarta from May to October 2023 on 32 operators. Data collection was carried out using a questionnaire using Total Sampling. Data processing was analyzed using univariate and bivariate analysis using Chi-Square. The research results showed that univariate analysis found that the highest proportion was bad behavior for 19 operators (59.4%), poor knowledge for 16 operators (50%), poor supervision for 16 operators (50%). The results of bivariate analysis showed that there was no relationship between knowledge and PPE use behavior (p-value-1.000), there was a relationship between supervision and PPE use behavior (p-value-0.031). It is recommended that field supervisors carry out more outreach efforts to increase knowledge and awareness and tighten supervision of gas station operators regarding occupational safety and health, especially regarding the use of PPE.